Effects of a Pre-Exercise Meal on Plasma Growth Hormone Response and Fat Oxidation during Walking - Shin, Y.H., Kyungpook National University, Daegu, Republic of Korea; Jung, H.L., Kyungpook National University, Daegu, Republic of Korea; Ryu, J.W., Kyungpook National University, Daegu, Republic of Korea; Kim, P.S., Yong In University, Gyeonggi, Republic of Korea; Ha, T.Y., Korea Food Research Institute, Gyeonggi, Republic of Korea; An, J.Y., Korea Food Research Institute, Gyeonggi, Republic of Korea; Kang, H.Y., Kyungpook National University, Daegu, Republic of Korea (Preventive nutrition and food science, 2013)
The purpose of this study was to determine the effects of a pre-exercise meal on the plasma human growth hormone (hGH) response and fat oxidation during walking. Subjects (n=8) were randomly provided with either 1 g/kg body weight of glucose in 200 mL water (CHO) or 200 mL water alone (CON) 30 min prior to exercise and subsequently walked on a treadmill at 50% of VO2max for 60 min. Plasma hGH concentrations were significantly higher in subjects who received CHO compared to those who received CON at 15 and 30 min. The fat oxidation rate in the CHO was significantly lower than the CON while walking for 5∼15, 25∼35 and 45∼55 min. Plasma FFA levels were also significantly lower in the CHO compared to the CON at 30, 45 and 60 min. Plasma glucose levels in the CHO were significantly lower while plasma insulin levels were significantly higher than in the CON at 15 and 30 min. Therefore, the results of this study suggest that the elevation of plasma hGH levels due to the intake of a pre-exercise meal may not be strongly related to fat oxidation and plasma free fatty acid (FFA) levels during low-intensity exercise